Addressing the inter‐individual variation in response to consumption of plant food bioactives: Towards a better understanding of their role in healthy aging and cardiometabolic risk reduction. Issue 6 (15th November 2016) - Manach, Claudine; Milenkovic, Dragan; Van de Wiele, Tom; Rodriguez‐Mateos, Ana; de Roos, Baukje; Garcia‐Conesa, Maria Teresa; Landberg, Rikard; Gibney, Eileen R.; Heinonen, Marina; Tomás‐Barberán, Francisco; Morand, Christine
Abstract : This paper examines the main factors likely to affect the individual responses to consumption of plant food bioactives, including those affecting bioavailability or bioactivity related to cardiometabolic health, and presents perspectives for assessment and consideration of inter‐individual variability. Abstract : Bioactive compounds in plant‐based foods have health properties that contribute to the prevention of age‐related chronic diseases, particularly cardiometabolic disorders. Conclusive proof and understanding of these benefits in humans is essential in order to provide effective dietary recommendations but, so far, the evidence obtained from human intervention trials is limited and contradictory. This is partly due to differences between individuals in the absorption, distribution, metabolism and excretion of bioactive compounds, as well as to heterogeneity in their biological response regarding cardiometabolic health outcomes. Identifying the main factors underlying inter‐individual differences, as well as developing new and innovative methodologies to account for such variability constitute an overarching goal to ultimately optimize the beneficial health effects of plant food bioactives for each and every one of us. In this respect, this position paper from the COST Action FA1403‐POSITIVe examines the main factors likely to affect the individual responses to consumption of plant food bioactives and presents perspectives for assessment and consideration of inter‐individual variability.